2020
DOI: 10.3847/1538-4357/ab698b
|View full text |Cite
|
Sign up to set email alerts
|

Close-in Exoplanets as Candidates for Strange Quark Matter Objects

Abstract: Since the true ground state of the hadrons may be strange quark matter (SQM), pulsars may actually be strange stars rather than neutron stars. According to this SQM hypothesis, strange planets can also stably exist. The density of normal matter planets can hardly be higher than 30 g cm −3 . As a result, they will be tidally disrupted when its orbital radius is less than ∼ 5.6 × 10 10 cm, or when the orbital period (P orb ) is less than ∼ 6100 s. On the contrary, a strange planet can safely survive even when it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 148 publications
(143 reference statements)
0
12
0
1
Order By: Relevance
“…Such GWs may be recognized as originating from a "planet"-compact star system. Geng et al (2015) and Kuerban et al (2020) have suggested that GWs from such "planet"-compact star systems could be efficiently used to identify strange quark planets, because a normal matter planet will be tidally disrupted by the compact star when it is still further away so that no GWs are available (Geng et al 2015;Kuerban et al 2020). Here, we would like to further remind that the possibility that the "planet" is actually a PBH should be further repelled before finally identifying it as a strange quark planet.…”
Section: Summary and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Such GWs may be recognized as originating from a "planet"-compact star system. Geng et al (2015) and Kuerban et al (2020) have suggested that GWs from such "planet"-compact star systems could be efficiently used to identify strange quark planets, because a normal matter planet will be tidally disrupted by the compact star when it is still further away so that no GWs are available (Geng et al 2015;Kuerban et al 2020). Here, we would like to further remind that the possibility that the "planet" is actually a PBH should be further repelled before finally identifying it as a strange quark planet.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…However, a 1.4 M SS has a radius very similar to that of a normal NS with comparable mass, thus it is hard to distinguish between these two types of compact stars via observations (Geng et al 2015(Geng et al , 2021. An interesting method to identify strange quark objects is to search for very close-in binary systems containing a strange planet and a compact star (Geng et al 2015;Kuerban et al 2019Kuerban et al , 2020. When the orbital radius of a planet is less than ∼ 5.6 × 10 10 cm or the orbital period is less than ∼ 6100 s, then it cannot be a normal matter planet, but should be a strange planet, because the tidal force is too strong to allow any kinds of normal matter planets to stably exist there (Huang & Yu 2017;Kuerban et al 2019Kuerban et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers [1,2] renew the interest in strange quark matter SQM objects of planetary masses [3] as candidates for high density planets orbiting some pulsars. Also, SQM planets around neutron stars are proposed to be new sources of gravitational radiation that could be detected by new generation detectors [4].…”
mentioning
confidence: 99%
“…In [1,2] the pulsar PSR B1257+12 is proposed as one of the hosts of candidates for SQM planets. It is the first stellar object discovered to harbour three planets [9] of 4.3 M ⊕ , 3.9 M ⊕ and 0.025 M ⊕ .…”
mentioning
confidence: 99%